Effects of Age, Sex, and Comorbidities on the Pediatric Outcomes Data Collection Instrument (PODCI) in the General Population - Gates, Philip E. (J Pediatr Orthop, 2015)
BACKGROUND: The Pediatric Outcomes Data Collection Instrument (PODCI) is an outcomes assessment tool developed to allow measurement of health-related quality of life in children with disorders having musculoskeletal impact. The instrument was tested by Hunsaker and colleagues on a large population-based sample of children (n=5300), and partial results of that survey were published in 2002. Further publication of the findings did not occur. The PODCI was designed to collect data on age, sex, comorbidities, race and ethnicity, makeup of the household, and other demographic data that could have an impact on function and psychosocial issues. This retrospective study evaluated the impact of age, sex, and health/comorbid conditions on the subscales of the PODCI. METHODS: Using the database that was developed by Hunsaker and colleagues for the American Academy of Orthopaedic Surgeons, a 1-way multivariate analysis of variance was conducted to determine effects of prior comorbid condition versus no prior comorbid condition on the dependent variables of the PODCI Upper Extremity Function, Transfers and Basic Mobility, Sports and Physical Function, Comfort, and Happiness scales by parent respondent. A follow-up analysis of the health/comorbid condition, age, and sex of the child on the PODCI subscales using independent samples t tests was performed. RESULTS: Significant differences in the PODCI subscales of Transfers and Basic Mobility, Sports and Physical Function, Comfort, and Happiness occurred between children with a prior comorbid condition versus no prior reported comorbid condition. The sex of the child with a comorbid condition versus without a comorbidity appears to affect the PODCI subscale scores except for the Upper Extremity Function subscale. PODCI scales show an initial increase with age. Age at plateau varies, as do patterns of scores after plateau, with gradual decreases in quality-of-life scales. CONCLUSIONS: With further exploration of the population-based database, it was possible to confirm that age, sex, and comorbidities do have an impact on the levels of functional and psychosocial assessments done with the PODCI. Assessments done with the PODCI should include the assessment of, and potential correction for, these variables. LEVEL OF EVIDENCE: Prognostic studies level II retrospective.